Chemical Composition of Essential Oils from Leaves and Fruits of Juniperus foetidissima and Their Attractancy and Toxicity to Two Economically Important Tephritid Fruit Fly Species, Ceratitis capitata and Anastrepha suspensa - Mehmet Kurtca; Ibrahim Tumen; Hasan Keskin; Nurhayat Tabanca; Xiangbing Yang; Betul Demirci; Paul E. Kendra (Molecules, 2021)
The present study analyzed the chemical composition of Juniperus foetidissima Willd. essential oils (EOs) and evaluated their attractancy and toxicity to two agriculturally important tephritid fruit flies. The composition of hydrodistilled EOs obtained from leaves (JFLEO) and fruits (JFFEO) of J. foetidissima was analyzed by GC–FID and GC–MS. The main compounds were α-pinene (45%) and cedrol (18%) in the JFLEO and α-pinene (42%), α-thujone (12%), and β-thujone (25%) in the JFFEO. In behavioral bioassays of the male Mediterranean fruit fly, Ceratitis capitata (Wiedemann), both JFLEO and JFFEO showed strong attraction comparable to that observed with two positive controls, Melaleuca alternifolia and Tetradenia riparia EOs. In topical bioassays of the female Caribbean fruit fly, Anastrepha suspensa (Loew), the toxicity of JFFEO was two-fold higher than that of JFLEO, with the LD50 values being 10.46 and 22.07 µg/µL, respectively. This could be due to differences in chemical components between JFLEO and JFFEO. The JFFEO was dominated by 48% monoterpene hydrocarbons (MH) and 46% oxygenated monoterpenes (OM), while JFLEO consisted of 57% MH, 18% OM, and 20% oxygenated sesquiterpenes (OS). This is the first study to evaluate the attractancy and toxicity of J. foetidissima EOs to tephritid fruit flies. Our results indicate that JFFEO has the potential for application to the management of pest tephritid species, and further investigation is warranted.